Legal Impacts of Ransomware Threats to Government Application: Srikandi - Ridho Bawana Jati; Ani Munirah Mohamad (CV. Cognispectra Publishing, 2025)
The ransomware threat affecting Indonesia is a serious one because it has crippled the government's public service platforms and the government's application called SRIKANDI, rendering them temporarily unusable. This ransomware attack also occurred because the government was careless in creating malware (security systems) that was easily breached by malicious hackers, allowing them to damage the operating system and steal data from the public service platform and the SRIKANDI application. The objective of this paper is to analyze the legal implications of ransomware threats on the government application SRIKANDI. The research method used for this writing is the normative method, which emphasizes literature review of previously existing problems and collecting relevant literature according to the issues discussed. The data collection technique for this research uses the library research technique (research library) by gathering relevant theories related to this issue, such as legal journals, books, or existing and relevant research. That in this ransomware attack issue, it has legal consequences for the suspect because it violates Indonesian legal regulations, namely the ITE Law (Electronic Information and Transactions) as stated in Article 32 Paragraph (1), Article 33, Article 48, and Article 49, and its enforcement refers to the Criminal Procedure Code (KUHAP) Article 30 Paragraph (2). The conclusion that can be drawn regarding the problems in this research is that the government is obliged to be vigilant by immediately restoring the operating system that has been hacked and the data stolen so that the Indonesian people can use it again. The government is also obligated to constantly strengthen malware (security systems) that are difficult for malicious hackers to breach, ensuring that the operating systems of government platforms and government-owned applications are always secure